Unraveling Challenges: Navigating Online Learning in Historical Studies at High School Level - Alamsyah; Pranoto, Nanda Wisnu; Egyir, Julius Kumi; Farrelly, Matthew (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to find out the problem Which appear on process learning online on eye lesson history in Senior High School3 Jambi City, find out the solutions taken by the school and teachers in overcoming the problems that exist in the online learning process in history subjects at Senior High School 3 Jambi City. Methodology: Researchers apply qualitative research methods, data collection techniques using observation, interviews and documentation. For deep data analysis study This consists from reduction data, displays data, take conclusion or verification. Main Findings: The results of the research conducted show that there are problems in the online history learning process , bothcaused by schools, teachers and students. The solution taken to overcome this problem was that the school collaborated with parents, teachers and related parties. Next, the teacher takes a policy of using learning applications that do not use up much internet data quota. Meanwhile, students make donations to help economically disadvantaged students in their families so that the learning process can run as an effort to achieve the competencies set out in the curriculum. Novelty/Originality of this study: This research not only identifies problems that arise during online learning, but also looks for solutions taken by schools and teachers. This approach provides a holistic view of online learning challenges and attempts to provide insight into how to overcome them. Thus, this research provides an in-depth and contextual view of the reality of online learning at Senior High School3 Jambi City, as well as concrete efforts taken to overcome the challenges faced in emergency situations such as the COVID-19 pandemic.